The importance of maternal diet quality during pregnancy on cognitive and behavioural outcomes in children: a systematic review and meta-analysis. Issue 9 (24th September 2017) - Borge, Tiril Cecilie; Aase, Heidi; Brantsæter, Anne Lise; Biele, Guido
Abstract : Objectives: This systematic review and meta-analysis provides a quantitative summary of the literature exploring the relationship between maternal diet quality during pregnancy and child cognitive and affective outcomes. We investigate whether there are indications for robust associations and aim to identify methodological strengths and challenges of the current research to provide suggestions of improvement for future research. Design and participants: Relevant studies were identified through a systematic literature search in relevant databases. All studies investigating maternal diet quality during pregnancy in relation to child cognitive or affective functioning in children of elementary school age or younger were assessed for inclusion. Results: 18 relevant studies, comprising 63 861 participants were identified. The results indicated a small positive association between better maternal diet quality during pregnancy and child functioning. We observed publication bias and significant heterogeneity between studies, where type of diet classification, publication year and outcome domain together accounted for about 30% of this heterogeneity. Trim and fill analysis substantiated the presence of publication bias for studies in the affective domain and showed an adjusted effect size of Hedge's g=0.088 (p=0.0018) (unadjusted g=0.093 (p=0.03)). We observed no publication bias in the cognitive domain, where results indicated a slightly larger effect size (g=0.14 (p<0.0001)) compared with that of the affective domain. The overall summary effect size was g=0.075 (p<0.0001) adjusted for publication bias (unadjusted g=0.112 (p=0.0001)). Child diet was not systematically controlled for in the majority of the studies. Conclusion: The results indicated that a better maternal diet quality during pregnancy has a small positive association with child neurodevelopment, with more reliable results seen for cognitive development. These results warrant further research on the association between maternal diet quality during pregnancy and cognitive and affective aspects of child neurodevelopment, whereby it is crucial that future studies account for child diet in the analysis.